Attenuation of orthodontically induced inflammatory root resorption by using low-intensity pulsed ultrasound as a therapeutic modality- a systematic review - Sunil Kumar Vaddamanu; Fahad Hussain Alhamoudi; Rajesh Vyas; Vishwanath Gurumurthy; Yulia Siurkel; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Ultrasound is an effective tool for both diagnostic and therapeutic applications. As an imaging tool, ultrasound has mostly been used for real-time noninvasive diagnostic imaging. As ultrasound propagates through a material, a reflected radio-frequency (RF) signal is generated when encountering a mismatch in acoustic impedance. While traditionally recognized for its diagnostic imaging capabilities, the application of ultrasound has broadened to encompass therapeutic interventions, most notably in the form of Low-Intensity Pulsed Ultrasound (LIPUS). Low-Intensity Pulsed Ultrasound (LIPUS) is a form of mechanical energy transmitted transcutaneously by high-frequency acoustic pressure waves. The intensity of LIPUS (30 mW/cm2) is within the range of ultrasound intensities used for diagnostic purposes (1-50 mW/cm2) and is regarded as non-thermal, non-destructive, permeating living tissues and triggering a cascade of biochemical responses at the cellular level. The LIPUS device produces a 200 µs burst of 1.5 MHz acoustic sine waves, that repeats at a modulation frequency of 1 kHz and provides a peak pressure of 30 mW/cm2. Low-intensity pulsed ultrasound (LIPUS) forms one of the currently available non-invasive healing-enhancing devices besides electro-stimulation (pulsed electro-magnetic field, PEMF). This modality has been leveraged to enhance drug delivery, expedite injury recovery, improve muscle mobility, alleviate joint stiffness and muscle pain, and enhance bone fracture healing. Although LIPUS has been embraced within various medical disciplines, its integration into standard dental practices is still in its nascent stages, signifying an unexplored frontier with potentially transformative implications. Low-intensity pulsed ultrasound (LIPUS) has emerged as an attractive adjuvant therapy in various dental procedures, such as orthodontic treatment and maxillary sinus augmentation. Its appeal lies in its simplicity and non-invasive nature, positioning LIPUS as a promising avenue for clinical innovation. One particular area of interest is orthodontically induced inflammatory root resorption (OIIRR), an oftenunavoidable outcome of the orthodontic intervention, resulting in the permanent loss of root structure. Notably, OIIRR is the second most common form of root resorption (RR), surpassed only by root resorption related to pulpal infection. Given the high prevalence and potential long-term consequences of OIIRR, this literature review seeks to evaluate the efficacy of LIPUS as a therapeutic approach, with an emphasis on assessing its capacity to reduce the severity of OIIRR to a level of clinical significance. To conduct this systematic review, a comprehensive automated literature search was executed across multiple databases, including MEDLINE, Embase, PsycINFO, Web of Knowledge, Scopus, CINAHL, LILACS, SciELO, Cochrane, PubMed, trials registries, 3ie, and Google Scholar. Both forward and backward citation tracking was employed, encompassing studies published from database inception through January 2009 to April 2023. The review focused on randomized controlled trials (RCTs) that specifically evaluated the effects of low-intensity pulsed ultrasound therapy on orthodontically induced inflammatory root resorption (OIIRR), without restrictions of publication date. A stringent selection criterion was applied, and only studies demonstrating high levels of statistical significance were included. Ultimately, fourteen studies met the inclusion criteria and were subjected to further analysis. The overall quality of the included randomized controlled trials (RCTs) was rigorously assessed utilizing the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. This analysis revealed certain methodological limitations that posed challenges in drawing definitive conclusions from the available evidence. Despite these constraints, the review offers invaluable insights that can inform and guide future research. Specifically, it delineates recommendations for targeted populations, necessary interventions, appropriate outcome measures, suitable study designs, and essential infrastructure to facilitate further investigations. The synthesis of these insights aims to enhance the development and application of low-intensity pulsed ultrasound therapy within the field of dentistry, thereby contributing to improved patient outcomes.